Maqosid Syariah Sebagai Pijakan Konseptual dalam Pelaksanaan Pilkada 2020 di Masa Pandemi Covid 19 - Nailull Hidayah; Ali Trigiyatno (Manabia: Journal of Constitutional Law, 2022)
The COVID-19 pandemic that has hit the world has forced the Indonesian government to issue various policies to prevent the spread of COVID-19, such as the PSBB policy and the new normal system. The Pilkada implementation uses the direct principle, so it is said that the Pilkada implementation is an activity that invites a large crowd. This is certainly not in accordance with the government's initial policy which required people to avoid crowds in order to break the chain of transmission of COVID-19. This research is a type of normative juridical research using statutory and conceptual approaches. The results of this study are that the government's reason for establishing Pilkada policies during a pandemic is to fulfill the people's constitutional rights to be elected and vote and so that there is no vacancy in leaders in various regions. The existence of a health protocol in the Pilkada policy is a form of protecting the soul (hifdz nafs) and a policy to continue holding Pilkada during a pandemic to prevent budget swelling to maintain economic stability which means it is also a form of preserving assets (hifdz mal).